2010
DOI: 10.1038/ncb2112
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of the GTPase Rac1 is required for optimal cell migration

Abstract: The Rho-like GTPase Rac1 induces cytoskeletal rearrangements required for cell migration. Rac activity is regulated through a number of mechanisms, including control of nucleotide exchange and hydrolysis, regulation of subcellular localization, or modulation of protein expression levels1-3. Here, we identify the Small Ubiquitin-like MOdifier (SUMO) E3-ligase, PIAS3, as a new Rac1 interactor required for increased Rac activity and optimal cell migration in response to Hepatocyte Growth Factor (HGF) signalling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
137
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 38 publications
15
137
0
1
Order By: Relevance
“…These results suggest that overexpression of PIAS3 may contribute to aberrant migration and invasion of RA FLSs. Consistent with our findings, PIAS3 knockdown decreased directional migration of HEK293T cells (17). PIASy also enhanced migration of epithelial cells (16).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results suggest that overexpression of PIAS3 may contribute to aberrant migration and invasion of RA FLSs. Consistent with our findings, PIAS3 knockdown decreased directional migration of HEK293T cells (17). PIASy also enhanced migration of epithelial cells (16).…”
Section: Discussionsupporting
confidence: 81%
“…For example, PIASy enhances epithelial cell migration through alteration of C/EBPd nuclear localization and reduction of C/EBPd transcriptional activity (16). PIAS3 controls migration by SUMOylation of Rac1 (17). Although previous reports have shown the role of SUMO in synovial proliferation and inflammation of RA (18,19), it is still unclear whether PIAS proteins are involved in the pathogenic FLSs behavior observed in RA.…”
mentioning
confidence: 99%
“…The only Rho GTPase that is known to be regulated by SUMOylation is Rac1, which becomes more active following addition of SUMO close to its C-terminus. 38 Phosphorylation is another covalent modification that regulates Rho GTPases. Some protein kinases such as PKA, ROCK1, Src and Akt have been shown to phosphorylate RhoA, Rnd3 (RhoE), Cdc42 and Rac1, respectively.…”
Section: Regulation Of Rho Gtpases By Post-translational Modificationsmentioning
confidence: 99%
“…Castillo-Lluva showed that Rac1 can be sumoylated on lysine residues in the PBR, promoting its activation and the induction of cell migration and invasion. 137 This post-translational modification is distinct from Rac1 ubiquitylation, which occurs on Lys147 and triggers its degradation. 88 Preventing Rac1 sumoylation did not alter its localization to membranes, nor the binding to GEFs and effector proteins, but did reduce GTP binding.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%